Quantitative assessment of the hydrogen induced cracking for 2.25Cr-1Mo-0.25V steel under electrochemical charging conditions. (June 2021) - Wang, Y.F.; Hu, S.Y.; Tian, Z.Q.; Cheng, G.X.
Highlights: Cracks and blisters formed due to cathodic charging with a low internal pressure; HIC initiation is primarily related to MnS and Al2 O3 inclusions; Integrity of the inclusion/matrix interfaces may control the crack initiation. Abstract: Hydrogen induced cracking (HIC) sensitivity of a vanadium-modified high strength steel at room temperature was studied by hydrogen concentration measurement, post-failure analysis, and interface characterization. It was found that the HIC sensitivity was relatively low as indicated by the small number of surface blisters and the random occurrence of internal cracks. This is partially attributed to the low hydrogen pressure in the defects, resulting from the high hydrogen solubility of the material. The immune inclusions with no cracks were identified after severe charging condition featuring more intact interface, indicating that the integrity of the interface and the size of voids may control the crack initiation.